Effects of Different Tillage and Nitrogen Management Practices on Maize Yield Parameters, and Soil Properties in Mid Hills of Nepal - Pandey, Pushpa; Lamichhane, Akangksha; Shrestha, Ram Kumar; Khanal, Dipak (Agriculture Development Journal, 2025)
A field experiment was conducted in March 2022 at Lamjung Campus, Sundarbazar, Nepal, to study the effects of tillage and nitrogen management practices on soil properties, yield, and yield attributes of the Posilo Makai-1 variety of maize. Two tillage systems (ZT-zero tillage and CT-conventional tillage) and four nitrogen management approaches (N1-traditional farmer’s practice, N2-recommended dose of NPK fertilizer (RDF), N3-50% RDN from urea+50% from FYM (farmyard manure) + recommended dose of phosphorous and potassium, and N4-leaf color chart (LCC)-based application of nitrogen + recommended dose of phosphorus and potassium) as main-plot and sub-plot factors were replicated thrice in a split-plot design. Research results revealed that nitrogen management practices significantly affected yield attributes and yield of the maize. LCC-based nitrogen application produced the highest cob length (15.2 cm), cob diameter (40.70 cm), grains per row (29.7), ear weight (89.0 g), grains per cob (420.03), 100-grain weight (20.70 g), and grain yield (4913.89 kg/ha), while the lowest values for yield attributes and yield were reported from farmer’s practice with the lowest yield (3227.47 kg/ha). Although statistically similar, LCC-managed plots had higher residual soil nitrogen (0.15%), organic matter (2.83%), soil available phosphorus (11.97 kg/ha), and available potassium (142.44 kg/ha), with reduced soil acidity (pH 5.35). However, tillage systems showed no statistically significant effect on yield parameters, yield, and soil parameters. These findings suggest that LCC-based nitrogen management could be a better practice for sustainable soil management and resource conservation in the long run.